Effect of Wearing Style on Vitamin D and Bone Mineral Density in Postmenopausal Osteoporotic Women - Yeşim Gökçe Kutsal (Türk Osteoporoz Dergisi, 2011)
Aim: Vitamin D deficiency is one of the most important public health problems as a result of osteomalacia, osteoporosis, muscle pain disease, muscle weakness and increased risk of falls and fracture. Outfitting style effects the synthesis and blood levels of vitamin D. The aim of our study is to investigate the effect of outfitting style on blood vitamin D and bone mineral density in postmenopausal osteoporotic women. Materials and Methods: Fifty-five female patients who were diagnosed with osteoporosis were included in our study. These women were divided into two groups according to their clothing habits as veiled and unveiled. Data of all patients about menopause, exposure to sun light, dual energy x-ray absorptiometry results, blood calcium, phosphate, parathyroid hormone, 25-hydroxyvitamin D levels and osteoporosis treatment were recorded. Results: We found 25-hydroxyvitamin D level was significantly low in women with veiled dressing style (17,0±7,9 ng/ml in veiled and 33.9±22.0 ng/ml in unveiled patients, p<0.001). There was statistically significant correlations between 25-hydroxyvitamin D level and femur neck Z-scores, femur total bone mineral density, femur total T-score L1-L4 bone mineral density, femur neck bone mineral density for different seasons (p<0.05). Conclusion: Postmenopausal osteoporotic veiled women are more prone to vitamin D deficiency than unveiled women. Low concentration of 25-hydroxyvitamin D is accompanying further decrease in bone mineral density. Despite low concentration of 25-hydroxyvitamin D in veiled postmenopausal osteoporotic women, there is not direct correlation between wearing style and bone mineral density. (Turkish Journal of Osteoporosis 2011;17:85-8)